2013
DOI: 10.1017/jfm.2012.599
|View full text |Cite
|
Sign up to set email alerts
|

Initial growth of a disturbance in a boundary layer influenced by a circular cylinder wake

Abstract: The initial growth of a disturbance induced by a near-wall circular cylinder in a flat-plate boundary layer is experimentally investigated using both particle image velocimetry and hydrogen bubble visualization techniques. The secondary spanwise vortices appear in the near-wall region as a direct response to the outside passing wake vortices, consistent with previous studies on similar models (Pan et al., J. ). The streamwise variation of the total disturbance energy within the boundary layer shows a two-stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 32 publications
(71 reference statements)
12
39
1
Order By: Relevance
“…In a recent experimental study of He, Wang & Pan (2013), secondary vortices were also observed in the near-wall region for Re D = 1118. In this case the cylinder was not placed near the leading edge but downstream and right above the boundary layer in order to avoid problems of leading edge receptivity.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…In a recent experimental study of He, Wang & Pan (2013), secondary vortices were also observed in the near-wall region for Re D = 1118. In this case the cylinder was not placed near the leading edge but downstream and right above the boundary layer in order to avoid problems of leading edge receptivity.…”
mentioning
confidence: 83%
“…Further downstream, the profile near the wall surpasses that of the Blasius profile, indicating a boundary layer transition. As no uniform outer flow can be observed due to the existence of the wake, we adopt a definition of boundary layer thickness used in the studies of Sarkar & Sarkar (2009) and He et al (2013). In this definition, the height of the maximum streamwise velocity between the wall and the wake deficit region is the boundary layer edge (as indicated by the horizontal dashed lines for the profiles at x/D = 5 and 25).…”
Section: Mean Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an de-biasing noise-robust method based on solving the total least-squares problem was proposed by Hemati and Rowley (2015), which provides the unbiased dynamical approximations in the noise contamination circumstance. On the other hand, the fluid community has seen a vast boost of DMD applications in both numerical and experimental studies Schmid 2011;Pan et al 2011;Muld et al 2012;Ghommem et al 2014;He et al 2013;Tang and Jiang 2012;Sampath and Chakravarthy 2014).…”
Section: Introductionmentioning
confidence: 99%